Quantum Machine Learning: Bridging Quantum Computing and AI for Exponential Gains - Shashank Chaudhary (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Quantum Machine Learning (QML) represents a convergent frontier where quantum computing meets artificial intelligence, offering transformative possibilities for computational challenges. This article explores the fundamental concepts, current applications, and future prospects of QML, examining how it addresses classical computational bottlenecks through quantum mechanical principles like superposition and entanglement. It analyzes core quantum computing architectures including Quantum Neural Networks, Variational Quantum Circuits, and Quantum Kernel Methods, highlighting their potential advantages over classical approaches. The article discusses practical applications across drug discovery, cryptography, and optimization problems while acknowledging significant technical challenges such as quantum decoherence, limited qubit connectivity, and error correction requirements. Through a comprehensive examination of hardware development needs, algorithm design strategies, and application discovery pathways, this article provides insights into the future research directions necessary for achieving practical quantum advantage in machine learning applications.